2010
DOI: 10.1002/biof.96
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of protein kinase CK2 as a key target in cancer therapy

Abstract: Protein kinase CK2, a protein serine/threonine kinase, plays a global role in activities related to cell growth, cell death and cell survival. CK2 has a large number of potential substrates localized in diverse locations in the cell including, e.g., NF-κB as an important downstream target of the kinase. In addition to its involvement in cell growth and proliferation it is also a potent suppressor of apoptosis, raising its key importance in cancer cell phenotype. CK2 interacts with diverse pathways which illust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
166
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 179 publications
(171 citation statements)
references
References 96 publications
1
166
0
Order By: Relevance
“…CK2 has now emerged as a relevant therapeutic target for the treatment of cancer (e.g. prostate, mammary gland, lung, kidney, hematologic malignancies) [9]. Indeed, diverse strategies are developed to target CK2 [10], and to synthesize highly specific, selective and cell-permeable inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…CK2 has now emerged as a relevant therapeutic target for the treatment of cancer (e.g. prostate, mammary gland, lung, kidney, hematologic malignancies) [9]. Indeed, diverse strategies are developed to target CK2 [10], and to synthesize highly specific, selective and cell-permeable inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…The kinase is highly pleiotropic, with more than 300 substrates identified, and interacts with multiple signaling pathways (Meggio and Pinna, 2003;Duncan and Litchfield, 2008;Ruzzene and Pinna, 2010). CK2 kinase is considered one of the "master regulators" of the cell, playing a major role in processes related to cell growth, proliferation, death, and survival (Trembley et al, 2010). The kinase is constitutively active and ubiquitously expressed in all eukaryotes (Duncan and Litchfield, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…17) It was reported to be implicated in a series of physiological and pathological processes, including various cancers, 18) bone formation, 19) mouse globozoospermia, 15) embryonic morphogenesis, 20) and chronic intestinal inammation. 21) We have previously identified CK2 as a GN-related gene and indicated that CK2 could be a therapeutic target for treating GN.…”
Section: Discussionmentioning
confidence: 99%